2020
DOI: 10.1016/j.bbmt.2020.03.018
|View full text |Cite
|
Sign up to set email alerts
|

HLA-Haploidentical Hematopoietic Cell Transplantation for Treatment of Nonmalignant Diseases Using Nonmyeloablative Conditioning and Post-Transplant Cyclophosphamide

Abstract: Allogeneic hematopoietic cell transplant (HCT) is often the only curative therapy for patients with nonmalignant diseases; however, many patients do not have an HLA-matched donor. Historically, poor survival has been seen after HLA-haploidentical HCT because of poor immune reconstitution, increased infections, graft-versus-host disease (GVHD), and graft failure. Encouraging results have been reported using a nonmyeloablative T cellÀreplete HLA-haploidentical transplant approach in patients with hematologic mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 55 publications
0
22
1
Order By: Relevance
“…The highly immunosuppressive properties of alemtuzumab are particularly appealing in the setting of nonmalignant HSCT, where GvHD provides no clinical benefit and relapse of malignancy is not applicable. Indeed, none of our patients developed any signs of acute or chronic GvHD as compared to the relatively high rates of acute and chronic GvHD reported by Mallhi et al using a RIC conditioning without serotherapy [10]. Commonly used pediatric transplantation regimens include alemtuzumab doses of 0.5-1 mg/kg given over 3-5 days [12].…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…The highly immunosuppressive properties of alemtuzumab are particularly appealing in the setting of nonmalignant HSCT, where GvHD provides no clinical benefit and relapse of malignancy is not applicable. Indeed, none of our patients developed any signs of acute or chronic GvHD as compared to the relatively high rates of acute and chronic GvHD reported by Mallhi et al using a RIC conditioning without serotherapy [10]. Commonly used pediatric transplantation regimens include alemtuzumab doses of 0.5-1 mg/kg given over 3-5 days [12].…”
Section: Discussionmentioning
confidence: 47%
“…Recent reports focusing on haploidentical HSCT with PT-Cy in pediatric patients with nonmalignant diseases offer different promising approaches using a variety of conditioning regimens [6][7][8][9][10]. Klein et al reported HSCT of 11 children with nonmalignant disorders showing very good outcomes with limited GvHD, excellent engraftment outcomes and no treatment related mortality using a RIC regimen with fludarabine, melphalan and upfront serotherapy with alemtuzumab [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A well-established alkylating agent, cyclophosphamide has maintained its role in HSCT due to its highly immunosuppressive properties and the relative resistance of hematopoietic stem cells to this agent even the highest doses (8,10,11). Recent studies have utilized cyclophosphamide post graft infusion to improve the outcomes of haploidentical transplant procedures (12)(13)(14). The success of this strategy has probably entrenched this agent as a major element of transplant therapy.…”
Section: Cyclophosphamidementioning
confidence: 99%